1993
DOI: 10.1007/bf00166845
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different carbon sources on the synthesis of pectinase by Aspergillus niger in submerged and solid state fermentations

Abstract: A study was made to compare the production of pectinase by Aspergillus niger CH4 in solid-state (SSF) and submerged (SmF) fermentations. Production of endo-(endo-p) and exo-pectinase (exo-p) by SSF was not reduced when glucose, sucrose or galacturonic acid (up to 10%0) were added to a culture medium containing pectin. Moreover, both activities increased when concentrations of the carbon sources were also increased. In SmF, these activities were strongly decreased when glucose or sucrose (3%) was added to cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
64
2
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(79 citation statements)
references
References 14 publications
11
64
2
2
Order By: Relevance
“…Activities of PG produced by Bacillus sp strains were higher than those produced by Aspergillus niger (19), Aspergillus sp and A. niger ATCC20107 (16), Aureobasidium pullulans (10) and Tubercularia vulgaris (12). However, they were lower than those reported using Bacillus GK-8 (9).…”
Section: Discussionmentioning
confidence: 77%
“…Activities of PG produced by Bacillus sp strains were higher than those produced by Aspergillus niger (19), Aspergillus sp and A. niger ATCC20107 (16), Aureobasidium pullulans (10) and Tubercularia vulgaris (12). However, they were lower than those reported using Bacillus GK-8 (9).…”
Section: Discussionmentioning
confidence: 77%
“…The spores used to inoculate the cultivation medium were enumerated by direct counting using a Neubauer chamber as previously described by Solis-Pereyra et al (1993). The A. oryzae concentration, in grams of dry mass per liter, was gravimetrically determined by filtering a known volume of culture medium through 0.45-µm-poresize cellulose membranes (MILLIPORE, USA) and drying at 90 °C for 24 h.…”
Section: Methodsmentioning
confidence: 99%
“…Similar results were published by Teixeira et al (2000), who described a repression of endo-and exo-PG production in Aspergillus japonicus when concentrations of glucose, pectin and sucrose were above certain levels. Solis-Pereyra et al (1993) and Acuña-Arguelles et al (1995) also reported that an excess of glucose in solid media reduced the formation of pectinases by Aspergillus niger. These authors claim that this result was due to a strong drop in the pH of the medium rather than catabolic repression or growth inhibition.…”
Section: Introductionmentioning
confidence: 93%
“…Pectinase synthesis occurs in many microbial groups, however, for the industrial pectinase production, fungi are the most used group due to their high enzymatic excretion capacity (23). Pectinolytic enzyme synthesis is highly influenced by substratum, particularly, carbon and nitrogen sources (6), presence of pectin (24) and temperature (3). Santos et al (22) reported that the aeration rate affects the substratum temperature and recommend controlling it to avoid overheating and enzyme denaturation during SSC.…”
Section: Introductionmentioning
confidence: 99%